Spectrophotometric Determination of Trimetazidine Dihydrochloride in Pharmaceutical Preparations - Murthy, T.K.; Sankar, D.G.; Rao, Y.S. (Asian Journal of Chemistry, 2010)
Two simple and sensitive visible spectrophotometric methods (A and B) have been described for the assay of trimetazidine dihydrochloride(TMZ) either in pure form or in pharmaceutical formulations. These methods are based on the oxidation followed by complexation between TMZ and o-phenanthroline or potassium ferricyanide in presence of ferric chloride to form a coloured product with λmax at 510 nm and 760 nm for method A and B respectively. All the variables have been optimized and the reaction sequence is presented. The concentration measurements are reproducible within a relative standard deviation of 1.0% Recoveries are 97.9-101.75%.